2019
DOI: 10.1620/tjem.248.159
|View full text |Cite
|
Sign up to set email alerts
|

Historical, Current and Future Approaches to Surgery for Rhegmatogenous Retinal Detachment

Abstract: Rhegmatogenous retinal detachment (RRD) is a serious condition that can cause blindness without surgical treatment. RRD occurs when a retinal tear or hole allows fluid to accumulate below the retinal surface, causing the retina to separate from the underlying layers. RRD is difficult to treat because each case is unique, varying with the location, size, and duration of the detachment, as well as patient age. The first successful methods to reattach the retina in RRD used thermocautery to repair the detachment.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
35
0
3

Year Published

2020
2020
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 41 publications
(38 citation statements)
references
References 66 publications
0
35
0
3
Order By: Relevance
“… 8 Retinal detachment is difficult to treat because each case is unique, varying with the location, size, and duration of the detachment, as well as patient age. 9 There are several surgical approaches, such as scleral buckling (SB), PPV, and pneumatic retinopexy (PR); however, no consensus has been reached on which approach is ideal. 10 Thus, we found that FCVB displayed better results in retinal reattachment, which is consistent with previous studies.…”
Section: Discussionmentioning
confidence: 99%
“… 8 Retinal detachment is difficult to treat because each case is unique, varying with the location, size, and duration of the detachment, as well as patient age. 9 There are several surgical approaches, such as scleral buckling (SB), PPV, and pneumatic retinopexy (PR); however, no consensus has been reached on which approach is ideal. 10 Thus, we found that FCVB displayed better results in retinal reattachment, which is consistent with previous studies.…”
Section: Discussionmentioning
confidence: 99%
“…The primary method to reattach the retina is surgical treatment. [ 3 ] The effect of retinal reattachment surgery is mainly evaluated by the patient's visual and anatomic outcomes. [ 4 ] Although RD surgery is well developed, up to 10% of all cases require additional interventions to ultimately repair recurrent detachments.…”
Section: Introductionmentioning
confidence: 99%
“…Each one has characteristic advantages for certain patients. After vitrectomy, a tamponade with gas or silicone oil is required [ 3 ]. In some cases, visual results may be unsatisfying.…”
Section: Introductionmentioning
confidence: 99%